6th International Conference on the Development of Biomedical Engineering in Vietnam (BME6) - Vo Van, Toi; Nguyen Le, Thanh An; Nguyen Duc, Thang (IFMBE Proceedings, 2018)
Under the motto "Healthcare Technology for Developing Countries" this book publishes many topics which are crucial for the health care systems in upcoming countries. The topics include Cyber Medical Systems Medical Instrumentation Nanomedicine and Drug Delivery Systems Public Health Entrepreneurship This proceedings volume offers the scientific results of the 6th International Conference on the Development of Biomedical Engineering in Vietnam, held in June 2016 at Ho Chi Minh City.